ロガン チタイ ニ オケル ジユウ セイカツ セイ ダニ ノ ブンプ ミツド - 大山, 佳邦; オオヤマ, ヨシクニ; Ohyama, Yoshikuni (国立極地研究所, 1977)
P(論文) 南極の昭和基地付近の露岩地帯には,一見植生のない砂地にも3種の自由生活性のダニが分布している. 1976年の1月と2月に東・西オングル島,ラングホブデ,スカルブスネスの各露岩地帯で,直径6cm,深さ1cmのシャーレに一杯の砂を採取し,floatation法によりダニを分離し個体密度を調査した.出現したダニはほとんどNanorchestes antarcticusであり,これはすべて砂地で採取したためと考えられる.他の2種はTydeus erebusがラングホブデの雪鳥沢の下流で9個体, Protereunetes minitusが西オングル島で2個体発見されたにすぎない各露岩地帯での最高個体密度は東オングル島でシャーレ一杯の砂から57個体,西オングル島で75個体,スカルブスネスで82個体であった.またダニの個体密度と棲息場所の水分との関係を調べるため,沢の岸で水ぎわから1m間隔で採集を行った結果,水ぎわから2～3m離れた岸で,最高の個体数が観察された. Population density of free-living mites was surveyed in the ice-free areas of Ongul Islands, Langhovde and Skarvsnes in the vicinity of Lutzow-Holm Bay, Antarctica. Sampling of mites was carried out on the sandy ground without macrophytic vegetation quantitatively using a petri dish of 6 cm in diameter and 1 cm in depth in January and February 1976. Mites were isolated from the sand by the floatation method. The highest density of mite population in each ice-free area was as follows: 57 mites in a petri dishful of sand in East Ongul Island, 75 mites in West Ongul Island and 82 mites in Skarvsnes. A preliminary observation on the relationship between the population density and the habitat moisture was made along the margin of the Yukidori Valley in Langhovde. Sampling was made at 1 m intervals from the waterside. The highest density of mite population was observed at the sampling point 2-3 m away from the waterside. departmental bulletin paper